Andronov-Hopf Bifurcation for Relay Systems - O. A. Chernysheva (Моделирование и анализ информационных систем)
We describe the structure of a monodromy matrix of periodic solutions for relay systems that makes it possible to derive the general criterion for the orbital exponential stability of the cycle. The given theorem is used to develop an analog to the Andronov-Hopf bifurcation theorem.